Anticoagulation quality and clinical outcomes in multimorbid elderly patients with acute venous thromboembolism. Issue 177 (May 2019) - Lange, Naomi; Méan, Marie; Stalder, Odile; Limacher, Andreas; Tritschler, Tobias; Rodondi, Nicolas; Aujesky, Drahomir
Abstract: Background: Multimorbid patients with acute venous thromboembolism (VTE) are often excluded from clinical trials and little is known about their prognosis. Objectives: To examine whether multimorbidity is associated with adverse clinical outcomes and lower anticoagulation quality in older patients with VTE. Patients/Methods: We studied 991 patients aged ≥65 years with acute VTE in a Swiss prospective multicenter cohort study. A modified Charlson Comorbidity Index was used to measure multimorbidity, which was defined as the presence ≥2 of 17 predefined comorbid conditions. We examined the association between multimorbidity and recurrent VTE and major bleeding, adjusting for confounders and periods of anticoagulation. We assessed whether the percentage of time spent in the therapeutic international normalized ratio (INR) range varied by the number of comorbidities present. Results: Overall, 708 (71%) patients were multimorbid. Multimorbid patients had a higher 3-year cumulative incidence of recurrent VTE (16.8 vs. 10.8%; P = 0.056) and major bleeding (18.7 vs. 9.0%; P = 0.001) than non-multimorbid patients. After adjustment, multimorbid patients had a significantly higher risk of recurrent VTE (sub-hazard ratio [SHR] 1.66, 95% confidence interval [CI] 1.08–2.57) and a higher risk of major bleeding (SHR 1.55, 95% CI 0.96–2.50), although the latter failed to achieve statistical significance. With increasing numbers of comorbid conditions, patients spent less time in and more time above and below the therapeutic INR range. Conclusions: Multimorbid patients with acute VTE have not only a lower anticoagulation quality but also more complications. Clinical trials should explicitly enroll multimorbid patients to determine the optimal anticoagulation strategy in such patients. Highlights: The long-term prognosis of multimorbid patients with venous thromboembolism (VTE) is unknown. We prospectively followed-up 991 patients with VTE in a multicenter study (71% were multimorbid). Multimorbid patients had a higher risk of recurrence and a somewhat higher risk of major bleeding. Patients with higher numbers of comorbidities spent more time outside the therapeutic INR range.